2017
DOI: 10.1186/s41239-017-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Blended learning effectiveness: the relationship between student characteristics, design features and outcomes

Abstract: This paper investigates the effectiveness of a blended learning environment through analyzing the relationship between student characteristics/background, design features and learning outcomes. It is aimed at determining the significant predictors of blended learning effectiveness taking student characteristics/background and design features as independent variables and learning outcomes as dependent variables. A survey was administered to 238 respondents to gather data on student characteristics/background, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
311
4
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(446 citation statements)
references
References 30 publications
23
311
4
24
Order By: Relevance
“…On the other hand, a study by Bovermann et al (2018) suggested that an effective online learning environment should include the factor of gaming as it could result in participants being more motivated in learning and also increase their level of satisfaction. To add to that, Kintu et al (2017) asserted that for mobile learning to be effective and contribute to learners' increased academic performance, it has to include other factors such as learners' interest, learning design and learning outcomes, in which learners' needs and a proper learning framework have to be prepared. Contrarily, Drew and Mann (2018) held a negative view of mobile learning and the use of interactive mobile application in lessons as they believe it is unfitting, uncomfortable and unacademic concerning the learning experience.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a study by Bovermann et al (2018) suggested that an effective online learning environment should include the factor of gaming as it could result in participants being more motivated in learning and also increase their level of satisfaction. To add to that, Kintu et al (2017) asserted that for mobile learning to be effective and contribute to learners' increased academic performance, it has to include other factors such as learners' interest, learning design and learning outcomes, in which learners' needs and a proper learning framework have to be prepared. Contrarily, Drew and Mann (2018) held a negative view of mobile learning and the use of interactive mobile application in lessons as they believe it is unfitting, uncomfortable and unacademic concerning the learning experience.…”
Section: Problem Statementmentioning
confidence: 99%
“…The inconclusiveness on whether mobile learning can be a good driving force in teaching and learning, and how it can really be effective can perhaps be answered by filling in the gaps highlighted by some previous studies. For instance, Kintu et al (2017) suggested that besides the students' characteristics, mobile learning design features are good drivers towards an effective blended learning environment. Meanwhile, Barrs (2011) recommended that detailed guidance and explanation on how to use smartphones appropriately in classroom settings is imperative if meaningful learning is to take place.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to strengthen the incorporation of contextual elements of the professional profile which is being formed (Zabalza, 2009). In this sense, Lloréns, Espinoza, & Castro (2013), discuss the importance of proportionality in terms of times, technological resources, and tutorial support for individuals and groups that are also evident in the activities of the three groups, and that according to Kintu, Zhu, & Kagambe (2017) are elements of a sound teaching design that are significant predictors of the development of student skills using BL teaching models.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of blended learning model can improve student academic performance [22]. Some characteristics of the student's background (mental maturity, attitudes, computer mastery, competence, gender, and workload) can be used as a basis in implementing blended learning model [23]. It is expected that with the learning model, student learning activities can be facilitated well.…”
Section: ) Test Product Effectivenessmentioning
confidence: 99%